Kesadaran Lingkungan Calon Guru Kimia sebagai Nilai Karakter Pendidikan Lingkungan - Dimas Ridho; Wawan Bunawan; Eviyona Laurenta Barus (Jurnal Penelitian Pendidikan IPA, 2025)
Environmental awareness among preservice teachers is an essential component of environmental education, yet its development is often influenced by limited knowledge and insufficient integration of environmental issues in higher education. This study aims to analyze the level of environmental awareness of prospective chemistry teachers based on three dimensions: knowledge, attitude, and behavior. A quantitative descriptive design was employed involving 127 students selected through purposive sampling. Data were collected using a validated questionnaire with a 5-point Likert scale, and analyzed descriptively by determining mean scores and category levels. The results showed that environmental awareness was in the moderate category for the knowledge aspect (M = 3.31) and in the high category for both attitude (M = 3.72) and behavior (M = 3.67). These findings indicate that students demonstrate positive attitudes and environmentally responsible behavior despite having limited conceptual knowledge. The study concludes that strengthening environmental knowledge through integrated instructional strategies, exposure to scientific literature, and collaborative environmental programs is essential. Further research should explore intervention-based models to enhance environmental literacy and examine factors influencing awareness development across different teacher education programs.